2010
DOI: 10.1002/hed.21517
|View full text |Cite
|
Sign up to set email alerts
|

Classification of papillary thyroid microcarcinoma according to size and fine‐needle aspiration cytology: Behavior and therapeutic implications

Abstract: The diagnosis of papillary carcinoma using the preoperative biopsy enables a more precise oncological procedure with greater chance of biological cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
3
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
1
11
3
4
Order By: Relevance
“…Several authors have reported that PTMCs that have >5 mm in size had a higher incidence of lymph node involvement, capsule invasion and multifocality, compared with those ≤5 mm [29,36], whereas other studies have shown no differences [37]. In our study we demonstrated that tumor size (< or ≥5 mm) was an independent risk factor for extrathyroidal extension.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Several authors have reported that PTMCs that have >5 mm in size had a higher incidence of lymph node involvement, capsule invasion and multifocality, compared with those ≤5 mm [29,36], whereas other studies have shown no differences [37]. In our study we demonstrated that tumor size (< or ≥5 mm) was an independent risk factor for extrathyroidal extension.…”
Section: Discussioncontrasting
confidence: 44%
“…The increasing number of thyroid echography, more or less controlled, the increasing number of total thyroidectomies performed for multinodular goiter and a more careful sampling of the thyroid specimens are among the most important factors to be considered [2,5,[7][8][9]. Population-level data supports this hypothesis, by correlating the increasing thyroid cancer incidence to the increasing use of thyroid ultrasound and fine needle aspiration (FNA), that were introduced in the early 1980s for thyroid cancer diagnosis [2,4,36]. Udelsman et al have showed that 57% and 49% of the variability in the USA state-level incidence of thyroid cancer for males and females, respectively, can be explained by the regional variation in the density of endocrinologists, general surgeons and employment of cervical ultrasonography [10].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of mPTC tumors, multifocality was found in 15% to 16% of tumors (23). In our study, we found multifocality in 35% of mFVPTC tumors and 32% of mPTC tumors.…”
Section: Discussionmentioning
confidence: 87%
“…As ultrasound-guided FNA has been widely accepted as a diagnostic modality for small thyroid nodules, the incidence of PMC has increased steadily [31]. However, PMC could be a confusing factor in thyroid FNA.…”
Section: Discussionmentioning
confidence: 99%